Contradictions in client-centred discharge planning: through the lens of relational autonomy. (July 2015) - Durocher, Evelyne; Kinsella, Elizabeth Anne; Ells, Carolyn; Hunt, Matthew
Abstract Background: While client-centred practice has received wide support, it remains difficult to apply in many practice settings. Identified barriers include constraints on time, resources, and services imposed by healthcare policies. Healthcare professionals' prioritizing of client safety over (other) interests that clients may name may further restrict the application of client-centred practice. Discharge planning is one area where such considerations can conflict. Aim: This paper presents a secondary analysis of data examining the process of discharge in one Canadian rehabilitation setting. It examines how discourses of client-centred practice and of prioritizing safety were reflected in discharge planning with older adults and considers the implications of potential conflicts between these discourses. Method: Taking a critical bioethics perspective informed by relational autonomy theory, microethnographic case studies were used to examine discharge planning from the perspectives of older adult clients and healthcare professionals. Results: Healthcare professionals interpreted client-centred practice to require abiding by client wishes, as long as this was safe; furthermore prioritizing safety took precedence over other considerations in discharge planning. Conclusion and significance: Client-centred practice was not promoted in discharge planning processes in the research setting. Applying a relational autonomy lens to practice could promote approaches that better facilitate client-centred practice.